“At the mercy of a miserable ditch named the Kifisos”: The Changing Perceptions of the Natural Environment and the Contest with Nature through the History of Athens’ Main River - Glistras, Dimitris (The Historical Review/La Revue Historique, 2023)
The course of the Kifisos over the past two centuries seems like it has been on the ultimate path to disaster. Its natural riverbed, the bioclimate and the flora along its banks have ceased to exist, at least in the form that they were some decades after the Greek War of Independence. However, the history of the Kifisos is interesting not just because it is a space which enables us to observe the environmental damage done by man, but also because a great part of the Greek capital’s own history is written in its riverbed. Through the history of the Kifisos and the varying perceptions of the river over time, the article describes the progression from a natural environment to an urban reality.